POTENTIAL OF BAJRA [PENNISETUM GLAUCUM (L.) R. BR.] IN HEALTH AND DISEASE - Kavya, *N; Kavya, B; Rao V, Rama; Kumar R, Kishore; MN, Shubhashree; N, Shiddamallayya; Bhat, Sulochana (International Journal of Ayurveda and Pharma Research, 2016)
Bajra, also known as pearl millet, African millet or spiked millet, originated in Northern-Central Sahel of West Africa, was introduced 2500 years ago into Indian subcontinent. However, it is mentioned in Ayurvedic texts from 14th Century AD onwards as Nali under Truna dhanya or Kudhanya vargas. It is considered as a major source of Gluten free diet and is used in the management of Coeliac disease and other gluten allergy conditions worldwide. Indians are also including millet into their day to day diet in accordance with the global trend.  However the conditions of Gluten allergy and Coeliac disease are not common in Southern India. Hence, the necessity of Gluten free diet in South Indian Population is under question. It is hypothesized that excessive millet usage could be a reason behind thyroid dysfunction and goitre. Regular millet only diet may also lead to a nutrition deprived state in people who are not gluten sensitive. Ayurveda also emphasizes on avoidance of regular use of Kudhanyas. This review comprises different aspects of dietary inclusion of Bajra. The properties and usability of Bajra as a gluten free diet, utility of Bajra in populations which are not gluten allergic and the effects of Bajra on health and disease form the core of this review.